Strategy for the implementation of innovations in the logistics industry - Marcenko, Valentyn (Revista Conecta, 2025)
Logistics firms confront escalating regulatory scrutiny, shrinking labour pools, and rising customer expectations for transparency. Addressing these pressures demands more than scattered technology pilots; it calls for a coherent implementation strategy that turns innovation from isolated gadgets into systemic capability. This research synthesizes findings from twelve rigorously selected empirical studies and threads them with insights drawn from the dual-layer OnLogix–Excel Logistics transformation case. Through a systematic literature review was extracted five critical success factors—data-integration readiness, top-management sponsorship, modular SaaS architecture, continuous compliance automation, and user-centric change management—that consistently underpin performance gains across carrier sizes. Meta-analysis indicates average operating-cost reductions of 29 % and compliance-fine declines of 55 % when the factors co-occur, echoing the outcomes observed in early adopters of OnLogix. Practical guidance emerges for vendors, carriers, and policy actors alike. By converging academic evidence with practice-based knowledge, the study advances Logistics 4.0 theory and offers managers a calibrated checklist for de-risking innovation roll-outs.